Формат видів замітки в українській пресі - Кузнецова, Олена Д.; Kuznetsova, O.D. (Східноєвропейський національний університет імені Лесі Українки, 2015)
Для вибору журналістами найефективнішого виду замітки, з метою сприяння якісному повідомленню читацької аудиторії диференційовано замітки, розкрито поняття «формат жанру», «формат видів замітки», аргументована відмінність терміну замітка від понять: повідомлення, інформація, новина, сенсація, факт, переконливо доведено помилкове зарахування О. Тертичним у підручнику «Жанры периодической печати» до видів замітки малих форм інших жанрів: текстівки, анонсу, анотації, міні-рецензії, бліц-портрета, міні-огляду, міні-історії. In order to define formats of types of informational genre of news story, to raise the level of journalism, to improve the quality of content of mass media, for effectiveness of influence of periodicals on recipients, for more precise definition of terms of journalistic genres, for journalist’s competence and skill upgrading, the author of the article has systematized, defined, differentiated types of news stories of the Ukrainian press, specified formats of types of news stories, identified signs of difference from each other and from other genres. The author also has clarified the meaning of definitions: report, news item, piece of news, sensation, fact; has convincingly proved their abuse as synonyms for the term «news story», has disputed with Russian professor A. A. Tertychnyy, who in his textbook «Genres of periodicals» has related small forms of other genres: caption, annotation, mini review, blitz portrayal, mini survey, mini story towards the forms of news story.
Format of Types of News Story in the Ukrainian Press
Keywords: формат жанру; news story; формат замітки; format of journalistic genre; види заміток; format of news stories; ознаки поділу на види; types of news story; журналістські жанри; journalistic genres